Self-Service Customer Service Models in Libraries. Issue 4 (18th May 2016) - Sigwald, Richard
ABSTRACT: The intent of this research study is to analyze and evaluate the transition to a self-service customer service model with the Baltimore County Public Library (BCPL). The study uses customer satisfaction surveys with questions specifically aimed at the various self-service service points BCPL offers to its customers. The methodology also includes several interviews with managers and directors to gain more in-depth information about how the transition affected the whole library system, its policies and procedures, and staffing. The results of this study are intended to demonstrate the effectiveness of using a self-service model in a public library.